Locating and Losing the Self in the World : Cross-Cultural Reflections on Self-Awareness and Self-Transcendence. - Ishida, Masato (Cambridge Scholars Publishing, 2014)
Comparative philosophy brings into focus relationships found across philosophies of disparate cultures. In the contemporary globalizing world, this perspective is vital - it ensures that diverse voices have the opportunity to be heard and refines the understanding of the many varieties of philosophical thought. Philosophy departments around the world are beginning to see the import of this broader perspective. Recent years have seen tremendous growth in the areas of Chinese, Japanese, Indian ...